The role of ultrasound and magnetic resonance imaging for treat to target in rheumatoid arthritis and psoriatic arthritis. (13th September 2019) - Mandl, Peter; Aletaha, Daniel
Abstract: The treat-to-target (T2T) approach has revolutionized the way we treat patients with rheumatic and musculoskeletal diseases. Recent attention has focused on imaging techniques, in particular musculoskeletal ultrasound and MRI as a focus for T2T strategies. Recently, a number of randomized clinical trials have been performed that compared tight clinical control vs control augmented by imaging techniques. While the three published trials have concluded that imaging does not add to tight clinical care, implementing imaging into the T2T strategy has actual advantages, such as the detection of subclinical involvement, and information on joint involvement/pathology and may possess potential advantages as evidenced by certain secondary endpoints. This review examines the findings of these studies and discusses the advantages and disadvantages of incorporating imaging into the T2T strategy.